Uso de harina de soya (Glycine max)” en la Alimentación de tilapia - Mantilla Manobanda, Betsy Daniela (2021)
A documentary research was carried out with the aim of generating information on the use of soybean meal, which has had a great impact worldwide due to its quality in essential nutrients for a balanced diet. it is for this reason that it is used in different production programs, among which we will highlight the cultivation of tilapia, an outstanding production in Ecuador, where the reduction in costs is the greatest challenge looking for a food inclusion alternative where reproductive and economic benefits are obtained, which are very important parameters in all types of exploitation, due to the high prices of fishmeal due to its high demand, it is sought to replace it with vegetable flours, with soybean meal supplemented with amino acids (50%) reaching average lengths of 23.72 cm, which has shown to be able to substitute it up to 100% ( Aguinaga Chalacán 2019) without affecting the reproductive parameters of tilapia, in the same way, other vegetable sources have been sought to replace soybean meal due to the increase in its use. In a study on the substitution of soybean meal for Cannavalia ensiformes flour (0, 25, 50, 75, 100%) it was shown that the growth and survival of tilapia were affected with the increase of this product, having the advantage that with soybean meal it was not affected (Cruz Alvarado et al., 2017), likewise, a study for the substitution of soybean balance for Moringa (10, 20, 30% and control) gave as a consequence that good results were obtained with respect to its inclusion and benefits in the diet for fish (Del Rio San Andrés 2018) .